2020
DOI: 10.3906/bot-2004-10
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural response of wheat (Triticumaestivum L.) lines to potential allelopathy of Alstoniascholaris (L.) R. Br. leaf extract

Abstract: An investigation was carried out to evaluate the impact of the allelopathic effect of Alstonia scholaris leaf extract on morphoanatomical and physiological characteristics of 5 wheat lines. Three extract dilutions were prepared, viz. 0 (control), 15 and 30% of the aqueous extract and sprayed on wheat lines (3094, 5066, M5082, 7076 and A2011) at 15-day intervals until maturity from November 2017 to May 2018. All wheat lines responded differently to an allelochemical extract of A. scholaris. Disintegration of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
3
5
0
Order By: Relevance
“…The decrease in growth traits were mainly due to a decrease in storage tissue (cortical parenchyma), mechanical tissue (sclerenchyma), vascular tissue (xylem and phloem) and dermal tissue (epidermis), as reported by Golzardi et al (2015), Feitoza et al (2018) and Hameed et al (2020). Estimated response curves showed high plasticity of morphological, anatomical and physiological traits in response to different concentrations of allelochemicals.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The decrease in growth traits were mainly due to a decrease in storage tissue (cortical parenchyma), mechanical tissue (sclerenchyma), vascular tissue (xylem and phloem) and dermal tissue (epidermis), as reported by Golzardi et al (2015), Feitoza et al (2018) and Hameed et al (2020). Estimated response curves showed high plasticity of morphological, anatomical and physiological traits in response to different concentrations of allelochemicals.…”
Section: Discussionsupporting
confidence: 66%
“…In a pilot experiment, as already published in our earlier paper by Hameed et al . (2020), the allelochemical effects of Alstonia scholaris leaf extract were tested on five wheat lines (3094, 7076, A2011 3094 and M5082). Based on the findings of this experiment, three wheat lines, 3094, 7076 and A2011 were selected for testing their response to A. carambola L. (star fruit) leaf extract applied as foliar spray.…”
Section: Methodsmentioning
confidence: 99%
“…Metaxylem cell area decreased at concentrated treatments of shoot extract in C. arvensis and A. tenuifolius . As reported by many researchers, such as Hameed et al [ 40 ], a decrease in metaxylem area in wheat varieties is observed at a higher level of leaf extract of A. scholaris. However, an increase in the metaxylem cell area of A. tenuifolius at diluted shoot extract was consistent with the finding of Chen et al [ 41 ], who reported an increase in the metaxylem cell area and vascular bundle area at high salinity levels in wild barley.…”
Section: Discussionsupporting
confidence: 53%
“…An increase in metaxylem cell area in C. arvensis at concentrated shoots extract levels favors the stronger tolerance against the biotic stresses, as water and mineral translocation may be easier, and this was a crucial adaptation against harsh environments (Ruiz et al [ 44 ]). While the decrease in this parameter in A. tenuifolius was fully reinforced by Hameed et al [ 40 ], who described that leaf extract of A. scholaris caused a decline in the metaxylem cell area in wheat lines. Vascular bundle area reduction in A. tenuifolius was supported by Nassar et al [ 45 ], who affirmed the reduction in a vascular bundle area with the application of abiotic stress.…”
Section: Discussionmentioning
confidence: 93%
“…The crude extracts from the leaves of devil tree (A. scholaris) showed the allelopathic effects on seed germination and radicle growth against of two tested plants (Bidens pilosa and Lactuca sativa) (Wang et al, 2014). Hameed et al (2020) noted that the allelopathic effects of the crude extracts from the leaves of devil tree (A. scholaris) on the stem growth character and root area character in wheat for two choices, the first choice that focused, the crude extracts from the leaves of devil tree (A. scholaris) showed reduction in stem growth and exhibited reduction in root area of wheat as well as the second choice focused, the crude extracts from the leaves of devil tree (A. scholaris) caused the growth retardation of wheat and showed the tissue damage of wheat. Sawatdikarn et al (2011) impressed that the allelopathic activity from the leaves of devil tree (A. scholaris) showed the reduction of percentages of seed germination against mungbean and black gram) as well as the allelopathic activity from the leaves of devil tree (A. scholaris) exhibited the reduction of seedling growth interm of tem height, number of leaf, leaf width and leaf length against mungbean and black gram.…”
Section: Results and Dicussionmentioning
confidence: 99%